Creating Playful First Encounters with the Pre-Modern Past (Book collections on Project MUSE., 2023)
This collection explores playful ways of fostering creative engagements with the medieval and early modern past and its own literary and artistic products, especially among those new to their study.00As scholars and teachers of early English, the contributors cover literary and cultural material from a range of genres within the Old English, Middle English, Tudor, and Stuart periods and collectively delve into a shared interest in facilitating what we might loosely define as ?newcomer? or ?non-specialist? encounters with the past: initial, exploratory contact in which prior knowledge cannot be assumed, whether involving creative professionals, experts from other disciplines, undergraduate and school students, or members of the public. Considering artworks and installation, theatre and performance and curation practices, case studies offer practice-based examples of learning and engagement which proceed primarily through creative and playful approaches. The case studies are arranged into two broad groups: those which work through performance and theatrical play of various kinds, and those which work through playful practices of production and making. All share a perspective of irreverence, of vivid immersion, and of the possibilities of conjuring with the past.0.